An Overview of the Emergence of Plant Pathogen ‘Candidatus Liberibacter solanacearum’ in Europe - Vojislav Trkulja; Andrija Tomić; Slavica Matić; Nenad Trkulja; Renata Iličić; Tatjana Popović Milovanović (Microorganisms, 2023)
In this paper, a comprehensive overview of the ‘Candidatus Liberibacter solanacearum’ presence in Europe was provided. The analyzed findings revealed that, since the first appearance of this pathogen in Finland and Spain in 2008, it has spread to 13 new European countries. Therefore, ‘Ca. L. solanacearum’ has spread very quickly across the European continent, as evident from the emergence of new host plants within the Apiaceae, Urticaceae, and Polygonaceae families, as well as new haplotypes of this pathogen. Thus far, 5 of the 15 ‘Ca. L. solanacearum’ haplotypes determined across the globe have been confirmed in Europe (haplotypes C, D, E, U, and H). Fully competent ‘Ca. L. solanacearum’ vectors include Bactericera cockerelli, Trioza apicalis, and B. trigonica; however, only T. apicalis and B. trigonica are presently established in Europe and are very important for plants from the Apiaceae family in particular. Moreover, psyllid species such as B. tremblayi, T. urticae, and T. anthrisci have also been confirmed positive for ‘Ca. L. solanacearum’. Constant monitoring of its spread in the field (in both symptomatic and asymptomatic plants), use of sensitive molecular diagnostic techniques, and application of timely management strategies are, therefore, of utmost importance for the control of this destructive pathogen.